Structural And IR And Raman Spectral Analysis Of Cyclo(His-Phe) Dipeptide - Özel, Ayşen E.; Kecel, Serda; Çelik, Sefa; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
A study was carried-out to measure and calculate infrared (4000-400 cm(-1)) and Raman (3500-50 cm(-1)) spectra of cyclo(His-Phe) dipeptide, which has anticancer activity. Conformational preferences of cyclo(His-Phe) dipeptide are investigated using theoretical conformational analysis followed by DFT calculations. The calculations of cyclo(His-Phe) dipeptide, as a function of side chain torsion angles, enable us to determine its energetically preferred conformations. The DFT calculations predict that the boat conformation is energetically more stable than the planar conformation. The dimeric forms of cyclo(His-Phe) dipeptide are constructed by bringing together two identical cyclo(His-Phe) monomers in possible configurations and three energetically favorable dimeric structures are obtained. The vibrational normal modes and associated wavenumbers, IR and Raman intensities of the global conformers of monomeric and dimeric units of cyclo(His-Phe) are calculated by DFT method at either both B3LYP/6-31G(d,p) and B3LYP/6-31++G(d,p) levels of theory (for monomer) or only at B3LYP/6-31G(d,p) level of theory (for dimeric unit). The total energy distributions (TED) of the vibrational modes are calculated by using the scaled quantum mechanical force field (SQM FF) method. Complete vibrational assignments of the observed spectra were performed by the aid of computed vibrational data. The cis amide II band is observed at 1481 cm(-1) in the Raman spectrum of solid cyclo(His-Phe), which is in agreement with previously reported Raman results for solid cyclic dipeptides, where the DKP ring adopts a boat conformation. The combination of the experimental and calculated spectra provide an insight into the structural and vibrational spectroscopic properties of cyclo(His-Phe) dipeptide. The energies of highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of cyclo(His-Phe) are calculated by DFT method at B3LYP/6-31G(d,p) level of theory. HOMO is localized on histidine amino acid whereas LUMO is localized mostly on phenylalanine ring. The computed HOMO-LUMO energy gap corresponds to 6.3596 eV (146.65 kcal/mol). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Conformational Analysis; Cyclic Dipeptide; Density Functional Theory; IR and Raman Spectra; Histidine; Phenylalanine; Cyclo(His-Phe); Density-Functional Theory; Ab Initio Calculations; Crystal-Structure; Vibrational-Spectra; Cyclic Dipeptides; Conformational-Analysis; Dft Calculations; Aqueous-Solution; Solid-State; Diketopiperazine; Konformasyon Analizi; Halkalı Dipeptid; Yoğunluk Fonksiyonu Teorisi; IR ve Raman Spektrumları; Histidin; Fenilalanin; Siklo (His-Phe); Yoğunluk Fonksiyonel Teorisi; Ab Initio Hesaplamaları; Kristal Yapı; Titreşim-Spektrumlar; Halkalı Dipeptitler; Konformasyon Analizi; Dft Hesaplamalar; Sulu Çözelti; Katı Hal; Diketopiperazin